Climate analogs can catalyze cross-regional dialogs for US specialty crop adaptation - Chaudhary, Siddharth; Rajagopalan, Kirti; Kruger, Chad E.; Brady, Michael P.; Fraisse, Clyde W.; Gustafson, David I.; Hall, Sonia A.; Hoogenboom, Gerrit; Melnick, Rachel L.; Reyes, Julian; Stöckle, Claudio O.; Sulser, Timothy B. (Nature Publishing Group, 2023)
Communication theory suggests that interactive dialog rather than information transmission is necessary for climate change action, especially for complex systems like agriculture. Climate analogs—locations whose current climate is similar to a target location’s future climate—have garnered recent interest as transmitting more relatable information; however, they have unexplored potential in facilitating meaningful dialogs, and whether the way the analogs are developed could make a difference. We developed climate context-specific analogs based on agriculturally-relevant climate metrics for US specialty crop production, and explored their potential for facilitating dialogs on climate adaptation options. Over 80% of US specialty crop counties had acceptable US analogs for the mid-twenty-first century, especially in the West and Northeast which had greater similarities in the crops produced across target-analog pairs. Western counties generally had analogs to the south, and those in other regions had them to the west. A pilot dialog of target-analog pairs showed promise in eliciting actionable adaptation insights, indicating potential value in incorporating analog-driven dialogs more broadly in climate change communication.